On I and I^K-Cauchy nets and completeness - Pal, Sudip Kumar (Sarajevo Journal of Mathematics, 2024)
In this paper we study the concept of I^K-Cauchy nets which is more general form of I^*-Cauchy nets. We also investigate its relation with the concept of I-Cauchy nets and study the completeness of a uniform space in terms of I^K-Cauchy nets. Subsequently our results extend similar results of Das and Ghosal. 2010 Mathematics Subject Classification. Primary: 54A20; Secondary: 40A35, 54E15